Influence of prenatal stress on metabolic abnormalities induced by postnatal intake of a high-fat diet in BALB/c mice - Juárez, Yamila R. (2020)
Fil: Juarez, Yamila. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina